Glucose-Regulated Protein 78 in the Aqueous Humor of Patients with Diabetic Macular Edema - Moon Young Choi; Jin-woo Kwon (Journal of Diabetes Research)
Purpose. We identified the associations between levels of aqueous glucose-regulated protein 78 (GRP78) and systemic or ocular factors in patients with center-involving diabetic macular edema (CIDME). Methods. We measured the aqueous concentrations of GRP78, interleukin- (IL-) 1β, IL-2, IL-8, IL-10, and IL-17, placental growth factor, and vascular endothelial growth factor (VEGF). We explored the associations between aqueous GRP78 levels and those of other aqueous factors, optical coherence tomography (OCT) findings, and systemic parameters in CIDME patients. Results. In multivariate regression analysis, aqueous GRP78 levels were associated with aqueous VEGF levels (p=0.007), length of EZ disruption (p<0.001), and duration of diabetes (p=0.002). However, no significant relationship was observed between GRP78 levels and those of other systemic and ocular factors including inflammatory cytokines in the aqueous humor. In terms of responsiveness, the number of hyperreflective foci (≥8) was significantly associated with the responsiveness of three consecutive monthly intravitreal bevacizumab injections (OR=0.34, p=0.046), but not the aqueous GRP78 levels. Conclusions. Aqueous GRP78 levels correlated with VEGF levels in the aqueous humor and EZ disruption on OCT. However, GRP78 levels were not associated with those of inflammatory biomarkers in the aqueous humor or OCT findings. Additionally, GRP78 could not serve as a biomarker to predict short-term prognosis of anti-VEGF agent.